UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SEJARAH MELALUI MODEL PEMBELAJARAN GROUP INVESTIGATION PADA SISWA KELAS XI IPS 1 SMA ADIGUNA BANDAR LAMPUNG - Muhammad, Muhammad (LPPM STKIP PGRI Bandar Lampung, 2019)
This research was conducted in class XI IPS 1 of SMA Adiguna Bandar Lampung in the Even Semester of the 2015/2016 Academic Year with the purpose of this research was to increase the activity and learning outcomes of History. This research is a Classroom Action Research that is the process of learning problems in the classroom through self-reflection in an effort to solve these problems by carrying out various planned actions in real situations and analyzing each effect of the treatment. This research was designed in two cycles with each cycle consisting of the stages of planning, implementation, observation, evaluation and analysis and reflection of actions. The research subjects were 22 students of class XI IPS 1 of SMA Adiguna Bandar Lampung in the 2015/2016 Academic Year. Data collecting techniques using observation sheets, test techniques and documentation. The results showed an increase in learning activities and students’ learning outcomes each cycle, student learning activities in the initial conditions there were only 8 students or 36.36% increased to 14 students or 63.64% and 20 students or 90.91% in the last cycle. Thus, the average student learning outcomes also increased in each cycle from 62.25 increased to 72.05 in the first cycle and at the end of the second cycle increased to 79.55. This was also evidenced by the increase in classical learning completeness where in the initial conditions there were only 7 students or 31.82% increased to 63.64% or 14 students and 20 students or 90.91% in the second cycle. From the explanation above, it can be concluded that the use of a group investigation learning model can increase the activities and learning outcomes of Class XI IPS 1 at SMA Adiguna Bandar Lampung in the 2015/2016 Academic Year. It is expected that in the future, this learning model can be applied in the learning process in other subjects so that what the teacher's goal is to improve the quality of education is achieved.